Indonesian Plants with Potential as Anti-diabetes Mellitus Agent - Rachmat Hidayat; Lusia Hayati; Nita Parisa (HM Publisher, 2020)
Diabetes Mellitus (DM) is a degenerative disease that continues to increase in number in Indonesia and is a disease that is spread throughout the world due to unbalanced nutritional conditions. Treatment of diabetes mellitus is a chronic and lifelong treatment. Treatment of diabetes mellitus, such as the use of insulin and oral antihyperglycemia drugs, is relatively expensive, is used for a long time and can cause unwanted side effects. There are many plants that have potential as antihyperglycemia drugs. One of the active compounds that act as antihyperglycemia is flavonoids.Flavonoids derived from various types of plants studied are thought to act as antihyperglycemic agents. Flavonoids are known to have the ability to scavenge free radicals or act as natural antioxidants. The antioxidant activity of flavonoids is related to phenolic –OH groups which can capture or neutralize free radicals (such as ROS or RNS). Flavonoids can play a role in pancreatic tissue damage caused by DNA alkylation due to alloxan induction as a result of improving the morphology of the rat pancreas.